Channel load based interference‐aware scheduling in military communication environment. (25th October 2018) - Vignesh, V.; Premalatha, K.
Summary: This work is focused to improve the military communication by introducing Channel Load based Average Link Interference Estimation (CLAIE) which will assess the channel load level of every route path, thus the interference reduced communication can be guaranteed. Channel load metric is capable of identifying interference superior to the previous metrics specified in IEEE 802.11 networks. This routing metric attains greater performance, when measured in the environment affected with interference, which contains inadequate radio channel resources such as wireless mesh network. This research offers a sequence of formulas in order to calculate link‐interference, path‐interference, and node‐interference and, in addition, to choose the paths containing the least average link‐interference amid the source and target, and an interference‐aware routing protocol is presented. Paths identified by this protocol are likely to evade the places containing greater interferences, decreasing the amount of retransmissions of packet and collisions, bringing about greater network throughput and increased lifespan. We present this average link interference‐aware routing. The overall methodology is deployed in military communication environment. In the NS2 simulation environment, the complete assessment of the research technique is implemented and proved that the presented research technique gives improved result.